Religión o el encuentro de la vida consigo misma - San Román Gómez, Álvaro (2023)
This paper attempts to offer a comprehensive approach to the religious phenomenon, considering that religion—understood as the attitude that each life has towards the brute fact of life—constitutes an anthropological universal. I claim that there are three emotional places or types of vital pathos that allow sketching three basic modes of articulating the religious: the pathos of disenchantment, the tragic pathos, and the pathos of wonder. After discussing the dialogues, tensions, and transitions between these, the paper concludes with a vindication of wonder as the genuine experience of a strictly religious life—that is, a life reconciled with totality.